PENGARUH PENGGUNAAN MODEL TALKING STICK TERHADAP HASIL BELAJAR IPA SISWA KELAS V SDN 01 NAN SABARIS KABUPATEN PADANG PARIAMAN - Lelfita, Lelfita; Melia Syar’i, Elsy; Dasmita, Dasmita (Ensiklopedia of Journal, 2024)
This research was motivated by the low science learning outcomes, especially for class V students at SDN 01 Nan Sabaris Kabupaten Padang Pariaman. The factor causing low student learning outcomes is that teachers have not used creative and innovative learning models and the learning that takes place is still teacher-centered. The aim of this research is to determine the influence of the Talking Stick Model on the Science Learning Outcomes of Class V Students at SDN 01 Nan Sabaris Kabupaten Padang Pariaman. Type of experimental research with a Posttest Only Control Design research design. The population of this study were all fifth grade students at SDN 01 Nan Sabaris. The sampling technique in this research used Saturated Sampling, totaling 40 people. The data analysis technique used in this research is the analysis requirements test and hypothesis testing with the t test. Research results, the average value in the experimental class is 80.80, the average value in the control class is 69.2, showing the ttable price with a = 0.05 and dk 38, namely 1.68. From the research, it was found that t count = 3.36, because t count> t table so that Ha was accepted, meaning there was a difference in learning outcomes between learning using the Talking Stick Model and conventional learning. It can be concluded that there is an influence of the Talking Stick model on the science learning outcomes of class V students at SDN 01 Nan Sabaris Kabupaten Padang Pariaman.Keywords: Talking Stick Model, Science Learning, Science Learning Outcomes